Full-stack web development for auto-assessment platform - Lee, Jun Wei (Nanyang Technological University, 2022)
Assessments in educational institutions are essential for educators to evaluate the efficacy of instruction and a means for students to measure their individual progress. With the ongoing Covid-19 pandemic prevalent across the globe, many educational institutions have adopted online-based platforms for managing and administering assessments to their students. The School of Computer Science and Engineering of Nanyang Technological University is no exception. Presently, the SC1007 Data Structures and Algorithms course administers various assessments to students through the HackerEarth online platform. Although the platform is full-featured, it incurs a high cost to utilise, and it is preferable to have an in-house platform where complete control over all aspects of the system is possible.